The Pathology of Iranian Taxation Proceedings System - Fatemeh Kohan; Abolfazl Jafar Gholi Khani; Saeed Reza Abadi (Indonesian Journal of Law and Society, 2022)
In terms of legal and criminal law and criminology, damage to the tax system is one of the most important threats. In addition, the tax system faces more severe litigation challenges due to unprecedented and oppressive sanctions against Iran and the outbreak of COVID-19 and its devastating economic consequences. This study investigates the weaknesses, strengths, opportunities, and challenges of the tax proceedings system in Iran in an analytical-descriptive method. The pathology of an efficient tax proceedings system in Iran can help reduce the number of cases in the courts, collect useful information from the Iranian National Tax Administration (INTA) about the taxpayers' economic activities, increase taxpayers' satisfaction, and so on. The study finds that tax authorities should (1) enact the law on the types of taxes and rates, (2) delineate the legal and regulatory structure, (3) provide free or low-cost accounting services, (4) decree penalties for violators, (5) intensify inspections, (6) augment control programs to record the taxpayers’ records properly, (7) accurately and timely fill out income tax returns, and (8)Tax authorities should be informed of companies and individuals who declare their profits suspiciously and take the necessary measures. Moreover, our findings show that tax officials' professional and intimate behavior with taxpayers could effectively inform the guidelines, prepare profit and loss statements, and achieve taxable profit.